Factors Influencing the acceptance of SAKTI Application: Perceived Usefulness, Perceived Ease of Use, and Perceived Risk on State Financial Planning and Budgeting - Oktaviyani, Tri; Kuntadi, Cris (Dinasti Publisher, 2022)
Previous research or relevant research is very important in research or scientific articles. Previous research or relevant research serves to strengthen the theory and phenomena of relationships or influences between variables. This article reviews the factors that influence the acceptance of SAKTI, namely: perceived usefulness, perceived ease of use, and perceived risk, a study of state financial management literature. The purpose of writing this article is to build a hypothesis about the influence of variables that can be used in further research. The results of this literature review article are: 1) perceived usefulness affects the acceptance of SAKTI; 2) perceived ease of use affects the acceptance of SAKTI; and 3) perceived risk affects the acceptance of SAKTI.